Bones : skeletons and how they work - Jenkins, Steve, 1952- (New York : Scholastic Press, 2010)
A guide to human and animal skeletons provides informative comparisons while sharing such facts as the number of bones in the human body and the ways that skeletal structures work.
Large bones, small bones -- Bones, bones, bones -- That's a handful -- Arm yourself -- You're grounded -- Big foot -- Support group -- Bony protection -- That's a lot of ribs -- Got your back -- The long and short of it -- Head case -- Making connections -- Rib-it -- Jump! -- Moving on -- Some assembly required -- Congratulations! -- More about bones : facts, stories, history, and science.
Keywords: Skeleton -- Juvenile literature